PEMANFAATAN PENINGKATAN HASIL BELAJAR PADA SISTEM ELEKTRONIK POWER STEERING - Muhammad Setiawan Dwi Saputro; Ahmad Rozikin (Universitas Negeri Semarang, 2024)
This research aims to develop virtual demonstration media for a car power steering electronic overhaul simulation based on an Android mobile application, find out how appropriate the demonstration media is for learning effectiveness, and find out how well the user's understanding of the media used in the learning process increases.This research used development research methods with the ADDIE development model and product trials using a one-group pretest-posttest design which was tested on students at Semarang State University, majoring in engineering education, namely in the chassis system course with 30 respondents. The instruments used are questionnaires and tests. Material expert validity questionnaire and media expert validity questionnaire. For the test, 27 questions were used which had previously been tested for validity and reliability.The media validation results obtained a score of 174 out of 200 by material experts and a score of 170 out of 200 by media experts. The material expert's assessment reached 85.5% with the criteria